Semantic-stylistic features of the initial and final sentences of the text (on the example of the genre of the story) - Zhunusova, M.K.; Ordabaeva, Z.Z.; Alpysbaeva, A.K.; Ospanova, G.E. ("Акад. Е.А. Бөкетов ат. Қарағанды ун-ті" КЕАҚ баспасы, 2022)
The article provides that the initial and final sentences have a special function in the content of the text, are of particular importance in increasing the attention, interest, and passion of the reader's attention to the content of the text. The novelty of the article is to identify the linguostilistic integrity of the most basic elements in the text formation of the narrative genre, forming a single thought, which is in the study of the text formation. The purpose of the study is to analyze in the direction of disassembling and reconstructing the whole (in the service of the initial, final sentences), as a result of which, in practice, these elements form the law of integrity of the text as a whole. When conducting linguistic analysis of the text, the authors showed by analyzing specific examples that various patterns of holistic thought ultimately find solutions in the final sentences of the main thoughts, ideas, and conclusions of the narrative genre, and not just from their beginnings. It is clarified that emotionally expressive sentences are structures that are unique to initial sentences. It has been proven that such a structure, which immediately attracts the attention of the reader, can immediately cause a positive or negative reaction, is also distinguished by the function of creating a figurative image. It is established that the beautification techniques used in figuratively-expressively constructed initial and final sentences, borrowed from the realities of life, have a special function in figuratively conveying to the reader various situations related to man and society, environmental and natural phenomena, and the psychological state of a person.
Мәтіннің бастапқы және соңғы сөйлемдерінің семантикалық-стилистикалық сипаты (әңгіме жанры мысалында)
Семантико-стилистические свойства начальных и конечных предложений текста (на примере жанра рассказа)
Keywords: text; linguistic integrity; initial and final sentences; text elements; figurative and expressive means